Optimizing Government Sukuk to Minimize Foreign Debt: A Qualitative Study on Indonesia’s Fiscal Policy Shift - Fahmaninda Listiyani; Dewi Wulansari (Universitas Alma Ata, 2025)
Introduction: Foreign debt has increased the burden on the State Revenue and Expenditure Budget (APBN), leading to unsustainability. Islam, a religion of charity, provides solutions for all aspects of human life, including the fiscal economic system. State sukuk, also known as state Sharia Securities (SBSN), is a sophisticated Islamic financial product that can alleviate issues caused by interest-bearing foreign debt.Methodology: This work uses a qualitative methodology such as in-depth interviews and literature reviews.Results: This research paper results such challenges on enhancing the development of SBSN in Indonesia, such as lack of human resourcesâ€™ understanding of the Islamic economic system, limited knowledge of the public regarding sharia investment instruments, the main economic drivers that are not yet the primary focus of state sukuk, inapplicability and inflexibility od SBSN, lack of SBSN issuance volume results in high issuance costs. Thus, based on some expertsÂ concluded in this research, it is concluded that there are several policy variables suggested, including increasing human resources, enhancing investor awareness, expanding financing to strategic sectors, developing SBSN innovations, and increasing SBSN issuance volume. Moreover, due to the numerous adverse impacts of foreign debt in accordance with Islamic best practices, this research proposes a transition from foreign loans to sukuk as the primary means of fiscal financing.Conclusion : Fiscal policies that cooperate with Islamic financial institutions are also necessary to help the government fund the national budget deficit and prevent usury. In result, The Ministry of Finance or Bank Indonesia should have an integrated system to address macroeconomic issues, not only based on conventional fiscal tools but also it need to adopt Islamic fiscal tools.